Drilling Technology : Fundamentals and Recent Advances - Astakhov, Viktor P.; Babu, J.; Castellano, Vitale Kyle; Chealvan, Hari; Davim, J. Paulo; Deshpande, A.S; Fayçal, Ameur Mohamed; Gaitonde, V.N; Habiba, Bougherara; Hejjaji, Akshay; Hilderbrand, Joshua; Karnik, S.R; et al. (Advanced Mechanical Engineering, 2018)
This book aims to provide recent information on advances in drilling technology. The use of advanced machines, appropriate strategies and special drilling tools can signifi cantly reduce the machining time required for drilling operations, and consequently the production costs, and improve the quality of the holes produced. For these reasons an improvement of the drilling technology is very important for the modern manufacturing industries. This book can be used as a research book for fi nal undergraduate engineering course or at postgraduate level. It can also serve as a useful reference for academics, researchers, mechanical, industrial, production, manufacturing and materials engineers, professionals in drilling technology and related matters.